Peer Educators in Religious Moderation and Mental Resilience through Strengthening Religious: Moderation Writing Classes - Budiman Budiman; San Putra; Prima Yanti Siregar; Putra Apriadi Siregar; Bagus Ramadi; Zahrani Nabila; Faiza Adinda; Putri Safira; Dhea Rizky Fitri Saragi; Ryanda Iqbaal Pradipta Widadi (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
This community service program addressed the need to strengthen religious moderation and mental resilience among students (santri) in Indonesia's diverse socio-religious context. Implemented at Pesantren Ulumul Qur'an, the initiative designed and evaluated an empowerment model that integrated two core components: the training of peer educators and the facilitation of a religious moderation writing class. The primary objective was to enhance the santri's knowledge, attitudes, and practical skills related to religious moderation and emotional management through a participatory, peer-based learning approach. The methods involved a series of structured activities, including training workshops, mentoring sessions, and facilitated writing and peer-review discussions, engaging a total of 31 santri. Data collected through pre- and post-program questionnaires revealed significant positive outcomes. The results showed marked improvements in several key areas: santri participation in writing activities increased, the consistent use of credible references in their writing rose from 25.8% to 38.7%, the practice of outlining arguments before writing grew from 38.7% to 67.7%, and the application of polite and inclusive language became more prevalent. Furthermore, the santri exhibited a strong consensus in supporting democratic values, interfaith cooperation (96.8%), and the protection of minority rights (96.8%). In conclusion, this service program effectively demonstrates that a model combining peer education and critical literacy through writing is a powerful tool for fostering a generation of santri who are not only knowledgeable and resilient but also active promoters of moderation and harmony in society. Keywords: Religious Moderation, Peer Educator, Writing Class, Santri, Community Empowerment.